2021
DOI: 10.3390/en14185791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subsurface Heat Capacity through Oscillatory Thermal Response Tests

Abstract: Two methods are currently available to estimate in a relatively short time span the subsurface heat capacity: (1) laboratory analysis of rock/soil samples; (2) measure the heat diffusion with temperature sensors in an observation well. Since the first may not be representative of in-situ conditions, and the second imply economical and logistical issues, a third option might be possible by means of so-called oscillatory thermal response tests (OTRT). The aim of the study was to evaluate the effectiveness of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Another common simple practice is to arbitrarily select a literature-based in-situ HC that matches the geological description of materials found in a borehole [7][8][9][10]. However, a study carried out by Giordano et al [11] revealed that typical uncertainty associated to the in-situ TD is about ± 40% when a conventional TRT is analyzed with an approximated HC for common geological materials (1.5 to 3.2 MJ m −3 K −1 ). Therefore, alternative field methods to infer heat storage properties is still need.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another common simple practice is to arbitrarily select a literature-based in-situ HC that matches the geological description of materials found in a borehole [7][8][9][10]. However, a study carried out by Giordano et al [11] revealed that typical uncertainty associated to the in-situ TD is about ± 40% when a conventional TRT is analyzed with an approximated HC for common geological materials (1.5 to 3.2 MJ m −3 K −1 ). Therefore, alternative field methods to infer heat storage properties is still need.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative field methods to infer heat storage properties is still need. Oscillatory TRT (OTRT) proposed and discussed by, for instance, Oberdorfer [12], and applied by Giordano et al [11], have the potential to evaluate the in-situ TD and HC. Although this methodology is an important step taken towards the in-situ evaluation of this thermal property; it still remains complex because of the analysis of the oscillating temperature response and needs more improvement to significantly reduce uncertainty (currently on the order of ± 15%).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations